Characteristics, distribution, and children exposure assessment of 13 metals in household dust in China: A big data pilot study. (18th October 2021) - Li, Xu; Fan, Lin; Wang, Xinqi; Yang, Yuyan; Zhu, Yuanduo; Han, Xu; Li, Li; Ge, Tanxi; Liu, Hang; Qi, Jing; Gong, Shuhan; Zhang, Qing; et al.
Abstract: To explore the pollution characteristics of metals in household dust in China and their exposure to children, this study searched peer‐reviewed papers published during 1980–2020 and analyzed 30 eligible papers screened under the per‐decided strategy. We evaluated the sample‐weighted concentration (SWC) of each metal, explored the sources of metals, and presented the quantitative description of spatial‐temporary characteristics and children exposure to 13 metals with multi‐route under a general living scenario. The results showed the concentrations of 13 metals with a range of 0.89–29 090.19 mg/kg. The SWC of Cd in household dust from rural areas was 3.29 times of that from urban areas, while the SWC of Ni from urban areas was 3.71 times of that from rural areas. The results showed that four principal components were extracted, and the cumulative contribution rate reached 79.127%. The exposure dose of 13 metals to children aged 2–3 years was presented with the highest by ingestion. Metals such as Fe, Zn, and Mn posed inevitable health risk to children with high exposure. Countermeasures should be carried out to minimize the children exposure to metals in household dust urgently, such as the establishment of environmental health standard for household dust.